Myocardial adenine nucleotide concentrations and myocardial norepinephrine content in patients with heart failure secondary to idiopathic dilated or ischemic cardiomyopathy - Regitz, Vera; Fleck, Eckart (The American journal of cardiology, 1992)
It has been suggested that chronically reduced myocardial adenosine triphosphate (ATP) content causes contractile dysfunction in dilated cardiomyopathy. Because total adenine nucleotides (ATP, adenosine diphosphate and monophosphate) may reflect chronic changes in energy metabolism better than may ATP alone, myocardial ATP, and adenosine diphosphate and monophosphate were determined in endomyocardial biopsy specimens from 19 patients with dilated cardiomyopathy, and decreased left (30 ± 2%) and right (34 ± 3%) ventricular ejection fractions, and from 11 patients with ischemic cardiomyopathy (left ventricular ejection fraction 38 ± 3%), and compared with those from 28 normal control subjects (ejection fraction >55%) to assess myocardial energy metabolism in heart failure. Myocardial norepinephrine was measured simultaneously in the same biopsy specimens to assess if the myocardium studied for adenine nucleotide content was metabolically altered. Myocardial total adenine nucleotides as well as ATP levels in 19 patients with dilated cardiomyopathy (39 ± 3 and 23 ± 3 nmol/mg of noncollagen protein, respectively) were unchanged in comparison with those of control subjects (37 ± 4 and 23 ± 3, respectively); patients with ischemic cardiomyopathy were not significantly different (30 ± 3 and 19 ± 3, respectively). Myocardial norepinephrine in the same biopsy specimens from patients with dilated (5.8 ± 1.1 pg/μg of noncollagen protein) or ischemic (5.7 ± 1.3) cardiomyopathy was significantly decreased compared with that of normal control subjects (12 ± 1.1). Normal myocardial total adenine nucleotides and ATP levels together with decreased myocardial norepinephrine in the same biopsy specimens suggest that reduced availability of myocardial adenine nucleotides or ATP is not an early metabolic feature of heart failure nor the cause for the development of contractile dysfunction.